Manajemen pendidikan lingkungan hidup di sekolah adiwiyata mandiri: Studi kasus SMA Negeri 2 Banguntapan - Giharto, Tri; Mariah, Siti; Mundilarno, Mundilarno (Rafandha Press, 2024)
Background: Environmental issues such as climate change, pollution, deforestation, and biodiversity loss, which have been exacerbated by human activities, have become a global concern, where education plays a crucial role in raising awareness and fostering more environmentally conscious behavior in society. Purpose: This research aims to describe the management of environmental education in Adiwiyata Mandiri School at SMA Negeri 2 Banguntapan include planning, organizing, actuating, controlling, and the supporting and inhibiting factors. Method: This research is a qualitative approach conducted. Techniques of collecting research data are interview, observation and document analysis. The main informants are the Principal, Vice Principal, Environmental Coordinator. Supporting informants are teachers and students. Data analysis technique used in this research is qualitative analysis with stages of data collection, data reduction, data display and conclusion. Techniques of checking the validity of the data used in the research is data triangulation. Findings: Result of research indicated that management of Environmental Education in Adiwiyata Mandiri School at SMA Negeri 2 Banguntapan cover planning, organizing, actuating, and controlling have done well. Supporting factor is commitment of the school's residents to environmental education, qualified human resources, facilities and infrastructure, and cooperate with various stake holder. Inhibiting factors are the motivation in developing environmental education is still fluctuating, skills in integrating environmental education in subjects is still limited, and limited funds. The undertakings include new student orientation based on environment, and involving the school's residents in environmental-themed education and training activities.